Answer: No
Step-by-step explanation: no because one is negative 1 3/4 and the other one isint in the negatives
It is given in the question that
Point N(7, 4) is translated 5 units up.
And we have to find the coordinates of its image after this transformation.
Since the point translated up by 5 units, so the x coordinate remains same and we have to add 5 to y coordinate.
So the new coordinate after the transformation is
![N'(7+5,4) \\ N'(12,4)](https://tex.z-dn.net/?f=N%27%287%2B5%2C4%29%0A%5C%5C%0AN%27%2812%2C4%29)
And that's the required coordinate after the given transformation .
Answer:
(x-3)(x-2)
Step-by-step explanation:
x^2 -5x+6
What two numbers multiply to 6 and add to -5
-3 * -2 = 6
-3 -2 = -5
(x-3)(x-2)
Answer:
<em>The Graph is shown below</em>
Step-by-step explanation:
<u>The Graph of a Function</u>
Given the function:
![\displaystyle y=g(x)=-\frac{3}{2}(x-2)^2](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y%3Dg%28x%29%3D-%5Cfrac%7B3%7D%7B2%7D%28x-2%29%5E2)
It's required to plot the graph of g(x). Let's give x some values:
x={-2,0,2,4,6}
And calculate the values of y:
![\displaystyle y=g(-2)=-\frac{3}{2}(-2-2)^2=-\frac{3}{2}(-4)^2==-\frac{3}{2}*16=-24](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y%3Dg%28-2%29%3D-%5Cfrac%7B3%7D%7B2%7D%28-2-2%29%5E2%3D-%5Cfrac%7B3%7D%7B2%7D%28-4%29%5E2%3D%3D-%5Cfrac%7B3%7D%7B2%7D%2A16%3D-24)
Point (-2,-24)
![\displaystyle y=g(0)=-\frac{3}{2}(0-2)^2=-\frac{3}{2}(-2)^2=-\frac{3}{2}*4=-6](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y%3Dg%280%29%3D-%5Cfrac%7B3%7D%7B2%7D%280-2%29%5E2%3D-%5Cfrac%7B3%7D%7B2%7D%28-2%29%5E2%3D-%5Cfrac%7B3%7D%7B2%7D%2A4%3D-6)
Point (0,-6)
![\displaystyle y=g(2)=-\frac{3}{2}(2-2)^2=-\frac{3}{2}(0)^2=0](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y%3Dg%282%29%3D-%5Cfrac%7B3%7D%7B2%7D%282-2%29%5E2%3D-%5Cfrac%7B3%7D%7B2%7D%280%29%5E2%3D0)
Point (2,0)
![\displaystyle y=g(4)=-\frac{3}{2}(4-2)^2=-\frac{3}{2}(2)^2=-\frac{3}{2}*4=-6](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y%3Dg%284%29%3D-%5Cfrac%7B3%7D%7B2%7D%284-2%29%5E2%3D-%5Cfrac%7B3%7D%7B2%7D%282%29%5E2%3D-%5Cfrac%7B3%7D%7B2%7D%2A4%3D-6)
Point (4,-6)
![\displaystyle y=g(6)=-\frac{3}{2}(6-2)^2=-\frac{3}{2}(4)^2=-\frac{3}{2}*16=-24](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y%3Dg%286%29%3D-%5Cfrac%7B3%7D%7B2%7D%286-2%29%5E2%3D-%5Cfrac%7B3%7D%7B2%7D%284%29%5E2%3D-%5Cfrac%7B3%7D%7B2%7D%2A16%3D-24)
Point (6,-24)
The graph is shown in the image below
![\vec F(x,y,z)=(x^2+y)\,\vec\imath+(y^2+x)\,\vec\jmath+ze^z\,\vec k](https://tex.z-dn.net/?f=%5Cvec%20F%28x%2Cy%2Cz%29%3D%28x%5E2%2By%29%5C%2C%5Cvec%5Cimath%2B%28y%5E2%2Bx%29%5C%2C%5Cvec%5Cjmath%2Bze%5Ez%5C%2C%5Cvec%20k)
We want to find
such that
. This means
![\dfrac{\partial f}{\partial x}=x^2+y](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cpartial%20f%7D%7B%5Cpartial%20x%7D%3Dx%5E2%2By)
![\dfrac{\partial f}{\partial y}=y^2+x](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cpartial%20f%7D%7B%5Cpartial%20y%7D%3Dy%5E2%2Bx)
![\dfrac{\partial f}{\partial z}=ze^z](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cpartial%20f%7D%7B%5Cpartial%20z%7D%3Dze%5Ez)
Integrating both sides of the latter equation with respect to
tells us
![f(x,y,z)=e^z(z-1)+g(x,y)](https://tex.z-dn.net/?f=f%28x%2Cy%2Cz%29%3De%5Ez%28z-1%29%2Bg%28x%2Cy%29)
and differentiating with respect to
gives
![x^2+y=\dfrac{\partial g}{\partial x}](https://tex.z-dn.net/?f=x%5E2%2By%3D%5Cdfrac%7B%5Cpartial%20g%7D%7B%5Cpartial%20x%7D)
Integrating both sides with respect to
gives
![g(x,y)=\dfrac{x^3}3+xy+h(y)](https://tex.z-dn.net/?f=g%28x%2Cy%29%3D%5Cdfrac%7Bx%5E3%7D3%2Bxy%2Bh%28y%29)
Then
![f(x,y,z)=e^z(z-1)+\dfrac{x^3}3+xy+h(y)](https://tex.z-dn.net/?f=f%28x%2Cy%2Cz%29%3De%5Ez%28z-1%29%2B%5Cdfrac%7Bx%5E3%7D3%2Bxy%2Bh%28y%29)
and differentiating both sides with respect to
gives
![y^2+x=x+\dfrac{\mathrm dh}{\mathrm dy}\implies\dfrac{\mathrm dh}{\mathrm dy}=y^2\implies h(y)=\dfrac{y^3}3+C](https://tex.z-dn.net/?f=y%5E2%2Bx%3Dx%2B%5Cdfrac%7B%5Cmathrm%20dh%7D%7B%5Cmathrm%20dy%7D%5Cimplies%5Cdfrac%7B%5Cmathrm%20dh%7D%7B%5Cmathrm%20dy%7D%3Dy%5E2%5Cimplies%20h%28y%29%3D%5Cdfrac%7By%5E3%7D3%2BC)
So the scalar potential function is
![\boxed{f(x,y,z)=e^z(z-1)+\dfrac{x^3}3+xy+\dfrac{y^3}3+C}](https://tex.z-dn.net/?f=%5Cboxed%7Bf%28x%2Cy%2Cz%29%3De%5Ez%28z-1%29%2B%5Cdfrac%7Bx%5E3%7D3%2Bxy%2B%5Cdfrac%7By%5E3%7D3%2BC%7D)
By the fundamental theorem of calculus, the work done by
along any path depends only on the endpoints of that path. In particular, the work done over the line segment (call it
) in part (a) is
![\displaystyle\int_L\vec F\cdot\mathrm d\vec r=f(4,0,4)-f(4,0,0)=\boxed{1+3e^4}](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Cint_L%5Cvec%20F%5Ccdot%5Cmathrm%20d%5Cvec%20r%3Df%284%2C0%2C4%29-f%284%2C0%2C0%29%3D%5Cboxed%7B1%2B3e%5E4%7D)
and
does the same amount of work over both of the other paths.
In part (b), I don't know what is meant by "df/dt for F"...
In part (c), you're asked to find the work over the 2 parts (call them
and
) of the given path. Using the fundamental theorem makes this trivial:
![\displaystyle\int_{L_1}\vec F\cdot\mathrm d\vec r=f(0,0,0)-f(4,0,0)=-\frac{64}3](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Cint_%7BL_1%7D%5Cvec%20F%5Ccdot%5Cmathrm%20d%5Cvec%20r%3Df%280%2C0%2C0%29-f%284%2C0%2C0%29%3D-%5Cfrac%7B64%7D3)
![\displaystyle\int_{L_2}\vec F\cdot\mathrm d\vec r=f(4,0,4)-f(0,0,0)=\frac{67}3+3e^4](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Cint_%7BL_2%7D%5Cvec%20F%5Ccdot%5Cmathrm%20d%5Cvec%20r%3Df%284%2C0%2C4%29-f%280%2C0%2C0%29%3D%5Cfrac%7B67%7D3%2B3e%5E4)